Comparing time to recovery in wasting treatment: simplified approach vs. standard protocol among children aged 6–59 months in Ethiopia—a cluster-randomized, controlled, non-inferiority trial - Maru, Yetayesh; Tamiru, Dessalegn; Baye, Kaleab; Chitekwe, Stanley; Kifle, Yehenew G.; Lailou, Arnaud; Belachew, Tefera (Frontiers in Pediatrics, 2024)
Introduction: Wasting occurs when the body's nutritional needs are unmet due to insufficient intake or illness. It represents a significant global challenge, with approximately 45 million infants and children under 5 suffering from wasting in 2022.A cluster randomized controlled non-inferiority trial was conducted in three regions of Ethiopia. A non-inferiority margin of 15%, along with a recovery rate of 90% and a minimum acceptable recovery rate of 75%, were considered alongside an intra-cluster correlation coefficient of 0.05 and an anticipated loss to follow-up of 10% in determining the total sample size of 1052 children. Children with Sever Acute Malnutrition (SAM) in the simplified group received two sachets of Ready to Use Therapeutic Food (RUTF) daily, while the standard group received RUTF based on their body weight. For Moderate Acute Malnutrition (MAM) cases, the simplified group received one sachet of RUTF, whereas the standard group received one sachet of Ready to Use Supplementary Food (RUSF) daily. A non-parametric Kaplan-Meir curve was utilized to compare the survival time to recovery.Results: A total of 1032 data points were gathered. For SAM cases, the average length of stay was 8.86 (±3.91) weeks for the simplified protocol and 8.26 (±4.18) weeks for the standard protocol (P=0.13). For MAM cases, the average length of stay was 8.18 (±2.96) weeks for the simplified approach and 8.32 (±3.55) weeks for the standard (P=0.61). There was no significant difference (P=0.502) observed between the simplified protocol, 8 weeks (IQR: 7.06, 8.94), and the standard protocol, 9 weeks (IQR: 8.17, 9.83), among children with SAM on the median time to cure. There was no significant difference (P=0.502) in the time to cure between the simplified approach, 8 weeks (IQR: 7.53 -8.47), and the standard protocol, 8 weeks (IQR: 7.66, 8.34), among children with MAM. The survival curves displayed similarity, with the log-rank test not showing significance (P>0.5), indicating the non-inferiority of the simplified approach for cure time.The findings showed that the simplified and standard protocols demonstrated no significant differences in terms of the average duration of stay and time required for recovery.